Active Thumbs, Confined Bodies: Eluding the 'Insect' in Times of the Plague. Issue 1 (2nd January 2021) - El Maarouf, M. D.; Belghazi, Taieb; Fendler, Ute
Abstract : This paper examines games during the COVID-19 pandemic as ontological barriers or barzakhs (singular: barzakh ). The traditional meaning of barrier as separation is coupled with the Greek meaning of play as Poiesis (which may also be understood as describing acts of creation). We expand the semantics of 'barrier' so as to describe pandemic phenomena that exist at the points at which opposites meet: synthetic game and the world of real game; the infected and the healthy; the player and the character being played; life and death . Our perception of both home and the exterior world has changed significantly in the time of the plague. At-home gaming, far from signalling our modern confinement, enables moments in which we may challenge our imprisonment. To bring this idea home, we deploy barzakh as a moral imperative, a site of both necessary isolation and opportunities of engagement, proof of our need for both interaction and distance, a place for the enactment of our knowing and strategic waiting in relation to the pandemic. Through the term, we theorize the link between barrier and other similar categorical divides (distances, masks, gloves, borders and quarantines) which we activate during lockdown to work through our puzzlement, win the social game of civil goodness and to downplay, and ultimately survive, the pandemic of our times.